Estimating the effect of palliative care interventions and advance care planning on ICU utilization: a systematic review - Khandelwal, Nita; Kross, Erin K; Engelberg, Ruth A; Coe, Norma B; Long, Ann C; Curtis, J Randall (Critical care medicine, 2015)
We conducted a systematic review to answer three questions: 1) Do advance care planning and palliative care interventions lead to a reduction in ICU admissions for adult patients with life-limiting illnesses? 2) Do these interventions reduce ICU length of stay? and 3) Is it possible to provide estimates of the magnitude of these effects? We searched MEDLINE, EMBASE, Cochrane Controlled Clinical Trials, and Cumulative Index to Nursing and Allied Health Literature databases from 1995 through March 2014. We included studies that reported controlled trials (randomized and nonrandomized) assessing the impact of advance care planning and both primary and specialty palliative care interventions on ICU admissions and ICU length of stay for critically ill adult patients. Nine randomized controlled trials and 13 nonrandomized controlled trials were selected from 216 references. Nineteen of these studies were used to provide estimates of the magnitude of effect of palliative care interventions and advance care planning on ICU admission and length of stay. Three studies reporting on ICU admissions suggest that advance care planning interventions reduce the relative risk of ICU admission for patients at high risk of death by 37% (SD, 23%). For trials evaluating palliative care interventions in the ICU setting, we found a 26% (SD, 23%) relative risk reduction in length of stay with these interventions. Despite wide variation in study type and quality, patients who received advance care planning or palliative care interventions consistently showed a pattern toward decreased ICU admissions and reduced ICU length of stay. Although SDs are wide and study quality varied, the magnitude of the effect is possible to estimate and provides a basis for modeling impact on healthcare costs.